Wearable ehealth systems for personalised health management : state of the art and future challenges - Lymberis, Andreas; De Rossi, Danilo E. (Studies in health technology and informatics, 2004)
This book consists of papers describing developments and trends all over the world in the areas of smart wearable monitoring and diagnostic systems, smart treatment systems, biomedical clothing and smart fibres and fabrics.